2005
DOI: 10.1111/j.1600-0684.2005.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect indicator of transport stress in hematological values in newly acquired cynomolgus monkeys

Abstract: Indicators of transport stress were investigated in blood parameters of five male cynomolgus monkeys obtained from abroad. They underwent air and ground travel-related stress in transport cages for a 15-hour transit time. On arrival, hematological parameters of white blood cell count, red blood cell count, hemoglobin concentration, and hematocrit values were within the limits of reference range, indicating that these parameters were not typical changes derived from transport stress loading. An increase in neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 28 publications
5
46
0
5
Order By: Relevance
“…In the vehicle control group, the average plasma concentration of DBILI was approximately 3-fold lower than UBILI and TBILI. Lower baseline level of DBILI has also been reported by others (Kim et al, 2005) and observed in other independent cynomolgus monkey studies (.300 animals) (unpublished observation) and is within a similar range as in mice (van de Steeg et al, 2012) and humans (unpublished observation). A significant elevation of conjugated, unconjugated, and total bilirubin was observed in both the RIF and RIF/RSV treatment groups as compared with RSV alone and vehicle control groups, respectively.…”
Section: Resultssupporting
confidence: 58%
“…In the vehicle control group, the average plasma concentration of DBILI was approximately 3-fold lower than UBILI and TBILI. Lower baseline level of DBILI has also been reported by others (Kim et al, 2005) and observed in other independent cynomolgus monkey studies (.300 animals) (unpublished observation) and is within a similar range as in mice (van de Steeg et al, 2012) and humans (unpublished observation). A significant elevation of conjugated, unconjugated, and total bilirubin was observed in both the RIF and RIF/RSV treatment groups as compared with RSV alone and vehicle control groups, respectively.…”
Section: Resultssupporting
confidence: 58%
“…** p<0.05; significant difference between the AAPH-treated group and the no-treated group per genotype. the lymphocytes in the thymus cortex or by extending the neutrophil half-life (18,19). Therefore, to study the correlation between the N/L ratio and corticosterone concentration, the concentration of corticosterone was assayed in the serum from CMV/GFP-hSelM Tg and non-Tg rats using an ELISA kit to coat the specific antibody.…”
Section: Effects Of Selm Overexpression On the Activities Of Gpx And mentioning
confidence: 99%
“…All standard clinical chemistry and CBC parameters were collected for all samples, but for the purposes of this report, only the subset of parameters that were thought to be of clinical/experimental relevance and that seemed likely to be affected by transport, relocation and acclimatization (Bergeron et al, 2002; Kagira et al, 2007; Kim et al, 2005; Landi et al, 1982; McGlone et al, 1993; Schapiro, 2002; van Ruiven et al, 1998) were analyzed. These included, for clinical chemistry, levels of Alanine Aminotransferase (ALT), Alkaline Phosphatase (ALK Phos), Blood Urea Nitrogen (BUN), Cholesterol, Creatinine, Glucose, Lactate Dehydrogenase (LDH), Potassium, Total Protein, and Triglycerides.…”
Section: Materials Methods and Ethical Approvalmentioning
confidence: 99%
“…Koban and colleagues (Koban et al, 2010), Kim and colleagues (Kim et al, 2005), Honess and colleagues (Honess et al, 2004), and Watson and colleagues (Watson et al, 2005), have presented behavioral and/or physiological data on the effects of transport on cynomolgus macaques, rhesus macaques, and Garnett's bushbabies, respectively. The responses of all three species were indicative of negative changes in welfare state as a function of the transportation episode.…”
Section: Introductionmentioning
confidence: 99%